Pemanfaatan E-book sebagai Sumber Belajar pada Kurikulum Merdeka - Ningsih, Farikha Septia; Ulya, Hanum Kholidiya (Revorma: Jurnal Pendidikan dan Pemikiran, 2024)
Success in the learning process is the main thing that must be in an educational institution. E-book s have great potential in utilization as a learning resource in the Independent Curriculum, although they have benefits, the challenges that must be overcome cannot be ignored either. The purpose of this article is to discuss the utilization of E-book  as learning resources in the Independent Curriculum. We will review the potential and benefits of E-book , the challenges that must be faced, and the steps that need to be taken so that E-book  utilization is able to run well to improve the quality of learning in Indonesia. The research used in this article is a type of library research or literature review research with qualitative methods. Library research or literature review is a critical process for collecting, evaluating, and synthesizing literature relevant to the intended research topic. The results show that E-books could increase students' activity, motivation, creativity, and learning outcomes. However, steps need to be taken to ensure equitable access for all students so that the benefits of E-book s can be felt thoroughly. The utilization of E-book s as an independent learning resource is very influential on students, E-book s have a positive impact on increasing learning productivity and reducing the burden on educators in presenting information. However, drawbacks such as dependence on battery power and vulnerability to piracy also need attention in its implementation. Thus, the utilization of E-books as an independent learning resource for students requires a comprehensive approach to maximize its benefits. Keywords: E-book s, Learning Resources, Independent Curriculum